Analisis Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Sepatu Casual Carvil Pada Mahasiswa ITMI Medan - Sunday Ade Sitorus; William Parlindungan Sihombing (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
Technological developments that are increasingly rapid and advanced continuously pose challenges for business people, who must learn to use technology in addition to understanding how to meet changing consumer needs, because consumers play an active role in marketing. Companies can face changing environmental conditions that are constantly changing, they must be able to formulate long-term strategies. This is competition and competition to market someone's product which is important in the world of marketing and competition. The aim is to determine the effect of product quality, price, and promotion on the decision to purchase Carvil Casual Shoes for ITMI Medan students. The results that have been researched are that the quality of the product partially does not have a positive and significant influence on purchasing decisions. Price partially has a positive and significant influence on purchasing decisions. Promotion partially does not have a positive and significant effect on purchasing decisions. Product quality, price, and promotion simultaneously have a positive and significant effect on purchasing decisions for casual Carvil shoes for ITMI Medan students. Based on the test of the coefficient of determination (R2), it is known that the Adjusted R Square value = 0.319, meaning that the purchasing decision variable can be explained by the product quality (X1) and price (X2) variables of 31.9%, while the remaining 68.1% can be explained by the other variables. other variables.